2023
DOI: 10.1111/cns.14388
|View full text |Cite
|
Sign up to set email alerts
|

Combined behavioral and EEG evidence for the 70 Hz frequency selection of short‐term spinal cord stimulation in disorders of consciousness

Abstract: ObjectivesThis study investigated the prognostic effect of electroencephalography (EEG) instant effects of single spinal cord stimulation (SCS) on clinical outcome in disorders of consciousness (DOC) and the time‐dependent brain response during the recovery of consciousness prompted by SCS.MethodsTwenty three patients with DOC underwent short‐term SCS (stSCS) implantation operation. Then, all patients received the postoperative EEG test including EEG record before (T1) and after (T2) single SCS session. Subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The significance of the 71 Hz frequency has not been fully substantiated; nevertheless, intriguing results have emerged from studies examining disorders of consciousness. Zhuang and colleagues [43] demonstrated that stimulating the spinal cord at 70 Hz in patients in a vegetative state elicited a positive EEG response. This stimulation increased parietal-occipital connectivity and beta frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…The significance of the 71 Hz frequency has not been fully substantiated; nevertheless, intriguing results have emerged from studies examining disorders of consciousness. Zhuang and colleagues [43] demonstrated that stimulating the spinal cord at 70 Hz in patients in a vegetative state elicited a positive EEG response. This stimulation increased parietal-occipital connectivity and beta frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…of severe patients [146][147][148] and can save many lives by monitoring epileptic seizures, status epilepticus, and acute ischemic stroke in real-time [146,149]. Zhuang et al reported spinal cord stimulation may facilitate the recovery of consciousness, and they used an EEG test to predict the process [150]. Thanks to the boom in deep learning, many deep learning models are developed and combined with EEG to detect mental fatigue [151], Parkinson's disease [152], depression [153], schizophrenia [154,155], epilepsy [156][157][158], and neurocognitive disorders [159,160].…”
Section: Bioelectrical Sensorsmentioning
confidence: 99%
“…Recently, percutaneous short-term SCS has been reported to may be useful in the treatment of DoC ( Yang et al, 2022 ; Huang et al, 2023 ). This minimally invasive approach affords clinicians the ability to directly engage with neuronal circuits that may be responsible for the modulation of conscious states ( Zhuang et al, 2023 ). This treatment method implants electrodes into the body for a short time and is currently mainly used for diagnostic treatment.…”
Section: Introductionmentioning
confidence: 99%